Hubungan Status Gizi dengan Kejadian Pneumonia Pada Balita di RSUD Syekh Yusuf Tahun 2022 - Utami Murti Pratiwi; Asrul Abdul Azis; Najamuddin; Galib; Resky Liyani Syam (Rumah Sakit Ibnu Sina, Makassar, 2026)
This Acute infection known as pneumonia is one of the leading causes of death in children under five. One of the influential factors that can determine the susceptibility of toddlers to a disease is pneumonia. This study aims to determine the relationship between nutritional status and the incidence of pneumonia in children under five years of age at RSUD Syekh Yusuf Gowa Regency in 2022. This type of research is an observational analytic with a cross-sectional approach . The population of this study were all toddlers diagnosed with pneumonia at RSUD Syekh Yusuf Gowa Regency in 2022, totaling 259 toddlers. The study sample was 108 toddlers using purposive sampling technique . The data used were secondary data in the form of medical records. Statistical calculations used chi-square test analysis . The number of toddlers diagnosed with pneumonia with very poor nutritional status was 15 (17.4%), undernutrition was 28 (32.6%), good nutrition was 37 (43%) and the risk of overweight was 6 (7%). In this study, there was a significant relationship between nutritional status and the incidence of pneumonia in toddlers as evidenced by the chi-square hypothesis test and the p-value = 0.022. The conclusion from the results of the study is that there is a significant relationship between nutritional status and the incidence of pneumonia in toddlers at RSUD Syekh Yusuf Gowa Regency in 2022